Empowering English Language Learning: Unleashing the Potential of Cooperative Learning Model at SMKN 3 Takalar - Hudriati, Andi; Sulastri, Sulastri; Rahmat, Rahmat (Pascasarjana Universitas Negeri Makassar, 2023)
The primary aim of adopting the cooperative learning approach in the context of English language learning is to investigate the potential improvement in students' English language competency within the X TKJ 3 class at SMKN 3 Takalar. The study used a research methodology known as classroom action research, commonly referred to as PTK (Praktikum Tindakan Kelas). The research was conducted over a span of two cycles. The statistics about student learning activities during the initial session of cycle 1 reveals an average activity level of 74%. Following this, during the subsequent meeting, there was seen a rise in the mean activity level, reaching 84%. The data regarding the advancement of student learning activities during cycle 2 meeting 1 indicated an average increase of 91%, which subsequently escalated to 96% during meeting 2. The findings from the study on the impact of cooperative learning model on English language learning outcomes in cycle 1 indicated an average score of 72. Furthermore, it was noted that a significant proportion of students, specifically 50%, were able to successfully attain the intended learning outcomes. During the second cycle, a notable rise was observed, as shown by an average score of 81 or a completion rate of 100% among the student population. Therefore, it can be deduced that the utilization of cooperative learning models holds the capability to augment the outcomes of English language acquisition among students in class X TKJ 3 at SMKN 3 Takalar.